BACAAN IDGHAM DAN IZHAR MENURUT IMAM TUJUH (IMAM QIRAAT SAB'AH) - Suarni Suarni (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2017)
As for this article is explained about the reading of Imam seven in reading Izhar and Idgham. The readings of Izhar and Idgham are not only related to the law of dead or tanwin. But many other letters or other words to read with Izhar or Idgham. By the Seven Imams have their own rules in the reading, so that the reading can be divided into two namely Idgham Kabir and Idgham Shagir. While reading Izhar is read the reverse from the reading of Idgham.